Site Specific Ground Response Analysis for Quantifying Site Amplification at A Regolith Site - Bambang Setiawan (Indonesian Journal on Geoscience, 2017)
DOI: 10.17014/ijog.4.3.159-167A numerical model has demonstrated that it can simulate reasonably well earthquake motions at the ground level during a seismic event. The most widely used model is an equivalent linear approach. The equivalent linear model was used to compute the free-field response of Adelaide regolith during the 1997 Burra earthquake. The aim of this study is to quantify the amplification at the investigated site. The model computed the ground response of horizontally layered soil deposits subjected to transient and vertically propagating shear waves through a one-dimensional-soil column. Each soil layer was assumed to be homogeneous, visco-elastic, and infinite in the horizontal extent. The results of this study were compared to other studies and forward computation of the geotechnical dynamic parameters of the investigated site. The amplification triggered by the 1997 Burra seismic event was deduced. This study reveals the amplification factor up to 3.6 at the studied site.